TEACHING IN 21ST CENTURY: STUDENTS-TEACHERS’ PERCEPTIONS OF TECHNOLOGY USE IN THE CLASSROOM - Asri Siti Fatimah; Santiana Santiana (Script Journal: Journal of Linguistics and English Teaching, 2017)
The rapid growth of technology encourages teachers especially who teach English as a foreign language to use it while presenting material and giving instruction in the classroom. Technology, as the newest instructional media developed in this globalization era, presents situation which helps the students to have new authentic and meaningful learning experiences engaging their effort and behavior by providing more fun and effective learning atmosphere. In addition, it provides the opportunity for the students to work collaboratively and easily access the information that can supplement their learning experience. Those benefits become the central part of 21st century education which should be optimized in order to create sophisticated learning immersion and maximize the quality of students in the future. In this research, some media techologies are introduced to one hundred student-teachers having Technology Enhanced Language Learning class. Those media, Prezi as online software presentation, Glogster as visual online poster,Edmodo as online networking application, Toondooas online cartoon strip making and Goanimateas animated video creation, are known as web-based instructional media which  can be used by them to teach English as a foreign language. However, questionnaire and interview are used to obtain the data.  It  aims to investigate their perception while preparing their teaching by using those applications.